2020
DOI: 10.1108/nfs-11-2019-0349
|View full text |Cite
|
Sign up to set email alerts
|

Soy ice cream as a carrier for efficient delivering of Lactobacillus casei

Abstract: Purpose Among soy products, soy ice cream with neutral pH, high total solids contents and prebiotic oligosaccharides is an appropriate vehicle for probiotics. The purpose of this paper is to survey soy ice cream as a carrier for the efficient delivering of Lactobacillus casei, or L. casei. Design/methodology/approach Probiotic soy ice cream containing L. casei was produced via the powder of soy milk. The physicochemical and organoleptic properties of the product were assessed. Also, the viability of L. casei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The panelists who performed the organoleptic evaluation of desserts did not recognize any of the products as particularly outstanding. In the studies of Homayouni et al [14], no statistically significant differences were found in terms of the organoleptic evaluation between the Lactobacillus casei fermented plant-based ice cream (soybean) and the unfermented control product. On the other hand, in the studies by Norouzi et al [29], fermentation of soy ice cream with Lactobacillus paracasei had a positive effect on the organoleptic characteristics of desserts.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The panelists who performed the organoleptic evaluation of desserts did not recognize any of the products as particularly outstanding. In the studies of Homayouni et al [14], no statistically significant differences were found in terms of the organoleptic evaluation between the Lactobacillus casei fermented plant-based ice cream (soybean) and the unfermented control product. On the other hand, in the studies by Norouzi et al [29], fermentation of soy ice cream with Lactobacillus paracasei had a positive effect on the organoleptic characteristics of desserts.…”
Section: Discussionmentioning
confidence: 89%
“…There are substances in plant raw materials that act as a carrier for microorganisms, such as fiber, vitamins, and minerals, as well as lipids [13]. The literature review shows that frozen non-dairy desserts can be an appropriate food matrix for the incorporation of lactic acid bacteria, and the probiotic effect depends on the used raw material and the individual characteristics of a strain [14]. It was found that the use PBS (Lb1), while reviving the bacteria, had a positive effect on the increase in the number of LAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In fact, many studies show the technological and functional features of soy protein, as an emulsifying and gelling agent. 6,[9][10][11] Thus, soy protein has been applied in several food products, such as milk, 12,13 cheese, [14][15][16] yogurt, [17][18][19][20][21] ice cream 22,23 and burger. 24 However, to our knowledge, there are still few works concerning the use and effectiveness of soy protein-based systems as a carrier of an active compound.…”
Section: Introductionmentioning
confidence: 99%